The house is on fire - Beanland, Rachel (New York : Simon & Schuster, 2023)
Told from the perspectives of four people whose actions changed the course of history, this masterful work of historical fiction takes readers back to 1811 Richmond, Virginia, where, on the night after Christmas, the city's only theater burned to the ground, tearing apart a community.
Keywords: Richmond Theater (Richmond, Va.) -- Fire, 1811 -- Fiction; Theaters -- Fires and fire prevention -- Virginia -- Richmond -- Fiction; Fires -- Virginia -- Richmond -- Fiction; Life change events -- Fiction; Richmond (Va.) -- History -- 19th century -- Fiction; Virginia -- Social life and customs -- 19th century -- Fiction; Historical fiction